Pengaruh Citra Perusahaan dan Promosi terhadap Minat Menggunakan Hasanah Card Pada BSI KC Medan - Heny Liya Hasibuan; Saparuddin Siregar; Sugianto Sugianto (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The Hasanah Card is a new breakthrough in the sharia-based credit financing system with an interest-free scheme. There are various factors that influence people's interest in using hasanah cards, including corporate image and promotion. Referring to these two factors, this research was conducted with the aim of knowing how the influence of corporate image and promotion on public interest using hasanah cards. The method used in this research is quantitative research, with the number of respondents as many as 40 people and the data analysis techniques used are classical assumption test, multiple linear regression test, F test, T test and R square test. The results showed that the company's image and promotion had a positive and significant influence on people's interest in using hasanah cards at BSI KC Medan